Reforming territorial care in Italy: Evidence and lessons from European experiences - Panunzio, Michele Fernando; Montagna, Maria Teresa; De Giglio, Osvalda; Liguori, Giovanna; Triggiano, Francesco; Marcotrigiano, Vincenzo; di Pumpo, Marcello; Russo, Rachele Maria; Sbrogiò, Luca Gino; Cinquetti, Sandro (Annali di Igiene Medicina Preventiva e di Comunità, 2026)
Background: European health systems are increasingly reorienting toward primary and community-based care in response to population ageing, the rising burden of chronic diseases, and vulnerabilities exposed by the COVID-19 pandemic. In Italy, Ministerial Decree 77/2022 (DM 77/2022) introduces a substantial reconfiguration of the National Health Service through the establishment of Community Health Centers, Community Hospitals, and Territorial Operations Centers. The reform aims to enhance proximity and accessibility, promote multiprofessional collaboration, and strengthen the integration of health and social services. Nonetheless, Italy’s pronounced regional autonomy results in heterogeneous implementation, raising concerns about equity and uniformity of service provision.Methods: This study situates DM 77/2022 within a broader European framework by comparing territorial and community-based care models in Spain, Germany, and the Netherlands. The analysis explores organizational arrangements, governance structures, financing approaches, workforce models, strategies for health–social care integration, and levels of digital development.Results: Spain’s Atención Primaria features multidisciplinary teams, strong continuity of care, and advanced digital interoperability. Germany’s Bismarckian system relies on independent general practitioners, structured chronic disease management programs, and coordinated care networks. The Netherlands exhibits highly integrated chronic care supported by care groups (Zorggroepen), mature digital infrastructures, and systematic patient engagement. These models reveal both convergences and divergences in governance, financing, social care integration, and technological readiness. While Italy’s reform reflects European principles of person-centered, community-oriented care, persistent challenges include workforce shortages, uneven resource allocation, and regional variability.Discussion: Enhancing governance coherence, reinforcing health–social integration, and investing in digital infrastructure may strengthen the implementation of DM 77/2022. Insights from European counterparts could help reduce territorial disparities, with the Prevention Department potentially serving as a key coordinating actor. Despite limitations inherent to qualitative comparative analysis, the study offers a framework for cross-national learning and underscores the reform’s potential to advance a resilient and equitable community-based health system.